2009
DOI: 10.1007/s11142-009-9086-7
|View full text |Cite
|
Sign up to set email alerts
|

Are analysts’ earnings forecasts more accurate when accompanied by cash flow forecasts?

Abstract: We examine whether analysts' earnings forecasts are more accurate when they also issue cash flow forecasts. We find that (i) analysts' earnings forecasts issued together with cash flow forecasts are more accurate than those not accompanied by cash flow forecasts, and (ii) analysts' earnings forecasts reflect a better understanding of the implications of current earnings for future earnings when they are accompanied by cash flow forecasts. These results are consistent with analysts adopting a more structured an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
220
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(246 citation statements)
references
References 53 publications
22
220
4
Order By: Relevance
“…It is in the same context, as Call et al (2009) showed that forecasts of accounting earnings published by financial analysts are more accurate when accompanied by those of the operating cash flows. Also, they add that financial analysts seem understand better the time series properties of accounting income and its components, when they jointly forecast the earnings and cash flows.…”
Section: Introductionmentioning
confidence: 86%
“…It is in the same context, as Call et al (2009) showed that forecasts of accounting earnings published by financial analysts are more accurate when accompanied by those of the operating cash flows. Also, they add that financial analysts seem understand better the time series properties of accounting income and its components, when they jointly forecast the earnings and cash flows.…”
Section: Introductionmentioning
confidence: 86%
“…The presence of an analyst's cash flow forecast indicates the perceived importance of OCF and the commensurate scrutiny of reported OCF (DeFond and Hung 2003;Call et al 2009). Evidence also suggests that analysts' cash flow forecasts create capital market incentives to report higher OCF (DeFond and Hung 2003;Brown et al 2013;Call et al 2013).…”
Section: Motivation and Research Design 21 Determinants Of Ocf Classmentioning
confidence: 99%
“…6 Relatively unknown analysts looking to establish a reputation would welcome the exposure I/B/E/S provides. 4 An alternative disaggregation of earnings is cash flows and accruals (Call et al 2009). While important in its own right, we do not use this disaggregation because analysts tend to supply cash flow forecasts to I/B/E/S when earnings are uninformative (DeFond and Hung 2003).…”
Section: Economic Determinants Of the Supply Of Disaggregated Earningmentioning
confidence: 99%